Aerobic exercise on the treadmill combined with transcranial direct current stimulation on the gait of people with Parkinson's disease: A protocol for a randomized clinical trial - Moraca, Gabriel Antonio Gazziero [UNESP]; Orcioli-Silva, Diego [UNESP]; Legutke, Beatriz Regina [UNESP]; Gutierrez, Pedro Paulo [UNESP]; Sirico, Thiago Martins [UNESP]; Zampier, Vinicius Cavassano [UNESP]; Beretta, Victor Spiandor [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Barbieri, Fabio Augusto [UNESP] (Public Library of Science (PLoS), 2024)
Gait impairments negatively affect the quality of life of people with Parkinson's disease (PwPD). Aerobic exercise (AE) is an alternative to alleviate these impairments and its combination with transcranial direct current stimulation (tDCS) has demonstrated synergistic effects. However, the effect of multitarget tDCS application (i.e., motor, and prefrontal cortices simultaneously) combined with physical exercise on gait impairments is still little known. Thus, the proposed randomized clinical trial will verify the acute effects of AE combined with tDCS applied on motor and prefrontal cortices separately and simultaneously on gait (spatial-temporal and cortical activity parameters) in PwPD. Twenty-four PwPD in Hoehn & Yahr stages I-III will be recruited for this crossover study. PwPD will practice AE on treadmill simultaneously with the application of anodal tDCS during four intervention sessions on different days (* one week of interval). Active tDCS will be applied to the primary motor cortex, prefrontal cortex, and both areas simultaneously (multitarget), with an intensity of 2 mA for 20 min. For sham, the stimulation will remain at 2 mA for 10 s. The AE will last a total of 30 min, consisting of warm-up, main part (20 min with application of tDCS), and recovery. Exercise intensity will be controlled by heart rate. Spatial-temporal and cortical activity parameters will be acquired before and after each session during overground walking, walking with obstacle avoidance, and walking with a cognitive dual task at self-preferred velocity. An accelerometer will be positioned on the fifth lumbar vertebra to obtain the spatial-temporal parameters (i.e., step length, duration, velocity, and swing phase duration). Prefrontal cortex activity will be recorded from a portable functional near-infrared spectroscopy system and oxygenated and deoxygenated hemoglobin concentrations will be analyzed. Two-way ANOVAs with repeated measures for stimulation and moment will be performed. The findings of the study may contribute to improving gait in PwPD. Trial registration: Brazilian Clinical Trials Registry (RBR-738zkp7).